A Novel Femtosecond Laser‐Assisted Method for the Synthesis of Reduced Graphene Oxide Gels and Thin Films with Tunable Properties. Issue 14 (4th May 2016) - Ibrahim, Khaled H.; Irannejad, Mehrdad; Hajialamdari, Mojtaba; Ramadhan, Ali; Musselman, Kevin P.; Sanderson, Joseph; Yavuz, Mustafa
Abstract : Graphene and its functionalized derivatives are unique and multifaceted novel materials with a wide range of applications in chemistry, healthcare, and optoelectronic engineering. 3D graphene materials exhibit several advantages over 2D (monolayer) graphene for a variety of devices applications. Here a novel and effective room temperature technique is introduced to convert an aqueous graphene oxide solution into a reduced graphene oxide gel with tunable physical and chemical properties comparable to a monolayer graphene sheet, without the need for any additives or chemical agents. The femtogel is synthesized by exposing an ultrahigh concentration graphene oxide solution with single‐layer flakes to high intensity femtosecond laser pulses. The femtosecond laser beam is focused on the air/aqueous solution interface to enhance the vaporization of functional groups and water, enabling femtogel formation. By controlling the pulsed laser intensity, beam focal parameters, and pulse duration, it is possible to produce several milliliters of femtogel in as little as 8 min. Through initial optimization of the irradiation parameters, a thin film is produced from a femtogel that demonstrates a surface roughness less than 6 nm, and more than 95% reduction in OH absorbance, as compared to a thin film produced from the unexposed graphene oxide solution. Abstract : A reduced graphene oxide gel (femtogel) is fabricated using pulsed laser ablation in liquid. This novel technique involves focusing femtosecond laser pulses at the air/liquid interface of a high concentration single‐flake aqueous graphene oxide solution. The hydroxyl groups, carbonyl groups, and water molecules are removed to facilitate the gel formation. The gel properties can be tuned by controlling the processing parameters.